BillBuddy: AI-powered receipt capture and smart bill sharing for easy expense management - Suhaimi, Nur Athirah; Mohd Ariff, Nur Aqilah; Ahmad Zahar, Aime Aqilah; Sukri, Nur Mas Syahierah; Kamis, Rohaiza (2025)
Managing individual and shared financial responsibilities can be challenging, particularly during group activities like dining out or traveling with friends or coworkers. This study introduces BillBuddy, a mobile application designed to simplify personal budgeting and group expense management using Artificial Intelligence (AI) and Optical Character Recognition (OCR) technologies. By allowing users to scan receipts, the app automatically extracts, categorizes, and logs expense data, eliminating manual entry, reducing errors, and improving financial accuracy. Beyond individual tracking, BillBuddy enables users to create shared events, split costs equitably or proportionally, track contributions, and receive automated payment reminders, promoting transparency and reducing social friction. Combining smart receipt scanning with a collaborative expense-sharing platform, BillBuddy addresses everyday financial challenges, enhances budgeting habits, and supports fair, informed decision-making. As demand grows for accessible, user-friendly fintech solutions that encourage both social interaction and financial responsibility, BillBuddy demonstrates strong potential for widespread adoption in consumer markets and financial education settings.